I fraseologismi come fonte di errori nel contesto dell’immagine linguistica del mondo - Paliczuk, Aleksandra; Pastucha-Blin, Agnieszka (Neophilologica, 2017)
The present paper aims to highlight various problems encountered in teaching Italian to Polish students at the university level. Phraseological units, constituting the integral part of every language, deserve particular attention as far as teaching culture and mentality of a given nation is concerned. Our analysis is conducted within the framework of cognitive linguistics, with the emphasis on the notion of the Linguistic Picture of the World (as formulated by Jerzy Bartmiński). We take into consideration the role of knowledge of foreign cultural background, because its lack (or poor knowledge) in learning a foreign language can be the source of errors, especially in the case of idiomatic expressions.